Pengaruh Kepercayaan, Citra Merek, Keamanan Terhadap Minat Beli Tiket Pada Situs Traveloka - Vina Endah Susanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to examine the effect of trust, brand image, and security on ticket buying interest on the Traveloka site (a case study of UST Yogyakarta students). The population in this study used students of the economics faculty majoring in accounting and management at Sarjanawiyata Tamansiswa University Yogyakarta. The type of data in this study uses quantitative data types. The sample method in this study is non-probability and the sampling technique uses purposive sampling. The results of the research simultaneously show a significant value of 0.000 <0.05, which can be concluded that the variables of trust, brand image, and security simultaneously or together have an effect on purchase intention. While the results of the research partially from each variable, there are 2 variables that do not affect, namely the trust variable with a significant value of 0.653> 0.05, it can be concluded that trust has no effect on purchase intention and the security variable with a significant value of 0.070> 0.05 can be concluded that security has no effect on purchase intention. While the brand image variable has a significant value of 0.000 <0.05, it can be concluded that brand image has an effect on purchase intention. Keywords: Trust, Brand Image, Security and Purchase Intention